Kompetensi Guru Matematika Dalam Mengembangkan Kompetensi Matematis Siswa - Kurnia Putri Sepdikasari Dirgantoro (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2018)
Education can not be separated from two main factors; teacher and student. In the absence of either of these two factors, it is essentially not education. In Indonesia, education is still far from what is expected. This can be seen from the fact that there are difficulties of the graduates achieving decent work result in accordance with the level of education they are in. One of the causes of the low quality of education in Indonesia is because the competence of teachers as educators is still considered low when compared with the standards that have been prepared. This article will discuss the influence of teacher competence on student competence, especially in Mathematics learning.